VERBAL AND NON-VERBAL SIGNS IN STOP BULLYING POSTERS: AN EDUCATIONAL POSTERS ANALYSIS - Claudya Pratama Putri; I Putu Andri Permana (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
This research entitled ‘Verbal and Non-Verbal Signs in Stop Bullying Poster’ was conducted to find out the implicit meaning of verbal and non-verbal signs used in these posters. A poster is a work of art used as a media publication by an artist in the form of writing, image, or a combination of the two which aim to give information to the public. Verbal and Non-Verbal Signs in these posters are very important to analyze because there are implicit messages to stop bullying in these signs. In this research, the qualitative descriptive approach to find out the implicit meaning from the data and research difficulties by applying the theory of signifier and signified by Saussure (1983). A documentation approach was used to execute the data collecting procedures. The documents utilized to support this study used 5 posters about stop bullying obtained from the internet. The result of the 5 data used there are - verbal signs and - non-verbal signs.